The Role of Technology in Teaching Ending Sound –s/-es Pronunciation: EFL Perception - Maspufah; Afriyeni, Yeni; Ariati, Jumerli; Zuriati, Diana (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Pronunciation has been regarded as the most challenging aspect of language teaching and learning. EFL learners faced difficulties in perceiving, producing, and mastering the intricate sound patterns of a new language, which can lead to communication breakdowns and reduced intelligibility. The use of learners-made tutorial videos in teaching pronunciation might overcome some of these challenges. This research aimed to find out learners’ perception of the role of technology in teaching ending sounds –s/es pronunciation through learners' self-made tutorial video. The research used descriptive qualitative method. The sample was taken by purposive sampling technique. Ten learners from the first semester of 2023/2024 academic year from a private public college in Pekanbaru were taken as the sample. The instrument used to collect data was questionaire from google form. The data were analyzed by using three data analysis theories. After analyzing the data, it was found that technology helped learners to be more responsible in studying, gain more knowledge beyond what the lecturer taught in the class, learn independently, encourage them to exchange knowledge with their classmate, and improve their English skill through making self tutorial videos in pronouncing –s/-es ending sound. Thus, it can be concluded that learners had a positive perception on the role of technology in teaching pronunciation especially in pronouncing –s/-es ending sound. Regarding the positive perception on the role of technology in teaching ending sound –s/-es perception, it is suggested to lecturers as well as English teachers to optimize the role of technology in teaching not only ending sound –s/-es, but also other aspects of pronunciation.